Possible roles of neuropeptide/transmitter and autoantibody modulation in emotional problems and aggression - Værøy, Henning; Skar-Fröding, Regina; Hareton, Elin; Fetissov, Sergueï O. (Frontiers in Psychiatry, 2024)
The theoretical foundations of understanding psychiatric disorders are undergoing changes. Explaining behaviour and neuroendocrine cell communication leaning towards immunology represents a different approach compared to previous models for understanding complex central nervous system processes. One such approach is the study of immunoglobulins or autoantibodies, and their effect on peptide hormones in the neuro-endocrine system. In the present review, we provide an overview of the literature on neuropeptide/transmitter and autoantibody modulation in psychiatric disorders featuring emotional problems and aggression, including associated illness behavior. Finally, we discuss the role of psycho-immunology as a growing field in the understanding of psychiatric disorders, and that modulation and regulation by IgG autoAbs represent a relatively new subcategory in psychoimmunology, where studies are currently being conducted.